The Implementation of Religious Moderation in the Quran and Hadith Learning At Islamic Senior High Schools in Aceh - M.Chalis, M. Chalis; Suhaimi, Suhaimi; Sulaiman, Sulaiman (Universitas Islam Negeri Ar-Raniry Banda Aceh, Aceh, Indonesia., 2024)
This study aims to determine the implementation of religious moderation in Qur'an and hadith learning at State Islamic Senior High Schools in Aceh Province. This research employed a qualitative method, involving nine subjects: three principals and six teachers teaching in three State Islamic Senior High Schools (Madrasah Aliyah Negeri) in three districts and cities in Aceh. The subjects were selected purposively. Data collection were done by interviews, observation, and documentation. The research results indicated that the implementation strategy of religious moderation is conducted through the preparation of lesson plans, integration during the learning, exemplary approach, application of cooperative learning models, and habituation of religious moderation attitudes in the school routine programs. This study found that the implementation policy of religious moderation refers to the Ministry of Religion of the Republic of Indonesia and the 2020-2024 RPJM. In addition, the moderation values implemented in learning Al-Qur'an Hadith include nine values; At-Tawassuth, At-Tasamuh, Ash-Shura, Al-'Itidal, Al-Ishlah, Al-Muwathanah, Al-Qurdwah, Al-La'unf, and Al-'Itiraf al-'urf. The implementation of religious moderation in the schools has some obstacles due to lack of socialization, the heterogeneity of the students' backgrounds, the environment, and inadequate facilities and infrastructure. However, overall, implementing religious moderation in Qur'an and hadith learning is effective.